2013
DOI: 10.1093/humrep/det096
|View full text |Cite
|
Sign up to set email alerts
|

Risks associated with bacterial vaginosis in infertility patients: a systematic review and meta-analysis

Abstract: It needs to be recognized that most inferences drawn in our study rely on a limited number of studies, potentially, endangering the generalizability of our findings. Moreover, all studies on cause of infertility in relation to BV included had a cross-sectional design and, therefore, do not allow for causal inferences. Still, there is strong circumstantial evidence that supports a causal link between BV and tubal infertility. Studies with a longitudinal design, on the other hand, strongly support a relation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
170
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(184 citation statements)
references
References 4 publications
7
170
0
7
Order By: Relevance
“…This microbially mediated vaginal acidity provides an important barrier that restricts the colonization of potential pathogens (Boskey et al, 1999). Perturbations to the composition of the human vaginal microbiome are often associated with diseased states, including bacterial vaginosis (BV) (Fredricks et al, 2005;Oakley et al, 2008;Marrazzo et al, 2010;Srinivasan et al, 2010), susceptibility to sexually transmitted infectious diseases (Sewankambo et al, 1997;Wiesenfeld et al, 2003), tubal infertility (Wiesenfeld et al, 2012;van Oostrum et al, 2013) and adverse pregnancy outcomes (White et al, 2011;Ganu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This microbially mediated vaginal acidity provides an important barrier that restricts the colonization of potential pathogens (Boskey et al, 1999). Perturbations to the composition of the human vaginal microbiome are often associated with diseased states, including bacterial vaginosis (BV) (Fredricks et al, 2005;Oakley et al, 2008;Marrazzo et al, 2010;Srinivasan et al, 2010), susceptibility to sexually transmitted infectious diseases (Sewankambo et al, 1997;Wiesenfeld et al, 2003), tubal infertility (Wiesenfeld et al, 2012;van Oostrum et al, 2013) and adverse pregnancy outcomes (White et al, 2011;Ganu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…45 BV is highly persistent and recurrent after treatment. 6 However, the etiology of BV is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence in UI was 37.4% which is more or less similar to our results (42.5%). In a recent systematic review and a meta-analysis, 28 it was concluded that all studies on infertility in relation to BV included had a cross-sectional design and, therefore, do not allow for causal inferences. Our study and others 27 would support the concept of definite correlation between UI and BV.…”
Section: Resultsmentioning
confidence: 99%